INNOVATIVE LEARNING MANAGEMENT FOR DRIVING ORGANIZATIONAL VALUES BASED ON ANDRAGOGY: A CASE STUDY OF SUPPORT STAFF AT KAMPHAENG SAEN CAMPUS, KASETSART UNIVERSITY - Pluempan, Ruangsin (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research aimed to study an innovative learning management approach for driving organizational values based on andragogy theory in the context of support staff at Kasetsart University, Kamphaeng Saen Campus. The focus was on enabling adults in the organization to learn in ways that connect organizational values with actual work practices. A qualitative research methodology was employed using a four-cycle action research design consisting of planning, action, observation, and reflection. The participants were selected through purposive sampling and comprised 12 university administrators, 250 support staff, and 7 organizational values promotion facilitators. Data were collected through observation, in-depth interviews, focus group discussions, and reflective journals, and were analyzed using content analysis and data triangulation. The findings revealed that this learning management innovation helped enhance the capacity of support staff in four key areas: (1) the increase of awareness and appreciation of organizational values that are clearly linked to their own roles and responsibilities; (2) an improved ability to use organizational values as a framework for analyzing problems and co-designing solutions in both simulated and real work situations; (3) the formation of a culture of shared learning and continuous knowledge exchange grounded in intrinsic motivation; and (4) the development of concrete ways of applying organizational values in routine work through reflective practice and learners’ self-direction in line with andragogical principles. In conclusion, andragogy-based learning management innovation can transform organizational values from an abstract policy framework into observable work behaviours among support staff and can strengthen an organizational culture driven by adult learning in higher education institutions.